Galenic Lab-on-a-Chip concept for lipid nanocapsules production. Issue 27 (30th June 2021) - Rolley, Nicolas; Bonnin, Marie; Lefebvre, Guillaume; Verron, Sylvain; Bargiel, Sylwester; Robert, Laurent; Riou, Jérémie; Simonsson, Carl; Bizien, Thomas; Gimel, Jean-Christophe; Benoit, Jean-Pierre; Brotons, Guillaume; et al.
Abstract : Galenic-on-chip concept and nanomedicines production using additive manufacturing and microfabrication techniques. Abstract : The continuous production of drug delivery systems assisted by microfluidics has drawn a growing interest because of the high reproducibility, low batch-to-batch variations, narrow and controlled particle size distributions and scale-up ease induced by this kind of processes. Besides, microfluidics offers opportunities for high throughput screening of process parameters and the implementation of process characterization techniques as close to the product as possible. In this context, we propose to spotlight the GALECHIP concept through the development of an instrumented microfluidic pilot considered as a Galenic Lab-on-a-Chip to formulate nanomedicines, such as lipid nanocapsules (LNCs), under controlled process conditions. In this paper we suggest an optimal rational development in terms of chip costs and designs. First, by using two common additive manufacturing techniques, namely fused deposition modelling and multi-jet modelling to prototype customized 3D microfluidic devices (chips and connectors). Secondly, by manufacturing transparent Silicon (Si)/Glass chips with similar channel geometries but obtained by a new approach of deep reactive ion etching (DRIE) technology suitable with in situ small angle X-ray scattering characterizations. LNCs were successfully produced by a phase inversion composition (PIC) process with highly monodispersed sizes from 25 nm to 100 nm and formulated using chips manufactured by 3D printing and DRIE technologies. The transparent Si/Glass chip was also used for the small angle X-ray scattering (SAXS) analysis of the LNC formulation with the PIC process. The 3D printing and DRIE technologies and their respective advantages are discussed in terms of cost, easiness to deploy and process developments in a GALECHIP point of view.